Integrating Environmental Education into English Speaking Lesson Plan Designed by ELT Pre-Service Teachers in State Islamic University of Lampung, Indonesia - Misbah, Hasanul (International Journal on Advanced Science, Education, and Religion, 2024)
The decrease of environmental quality in Indonesia has been globally attentive to the world eyes. In responses to that, State Islamic University of Lampung introduced the university vision and missions to integrate the environmental issues into education, researches and community services. In university educational practices, the subject of ecolinguistics proposes the learning that helps students be aware of global and local environmental issues and be able to design eco-based lesson plans. The focus of the study was to investigate the integration of environmental education into the eco-based speaking lessons. The research methodology is qualitative with five participants selected through a purposive sampling process. The data were collected via semi-structure interview. According to the data analysis, it was revealed that not only the learning experiences assist them but also the students’ critical and creative thought matters most. In conclusion, to achieve the higher level of thinker, the students need to have more professional development so that the better products of pedagogical applications can be effectively delivered in the lesson plans. Keywords: Environmental Education, English Language Teaching, ELT Pre-Service Teachers, Speaking Lesson Plan